Externalities of economic sanctions on performance of intra-industry non-sanctioned firms: evidence from Zimbabwe - Sun, Jie; Makosa, Lewis; Yang, Jinkun; Yin, Fangyuan; Jachi, Moses; Bonga, Wellington Garikai (Wiley, 2022)
This paper investigates the effect of targeted economic sanctions by the United States and the European Union on the performance of intra-industry non-sanctioned firms. Using data of non-sanctioned firms listed on the Zimbabwe stock exchange during the period 2009–2018, our regression results show that non-sanctioned firms in the same industry as sanctioned firms perform better than ordinary non-sanctioned firms, signalling the positive competitive effect. A mediating test suggests that sanctions increase the market share of non-sanctioned firms in the same industry as sanctioned firms and subsequently increase their performance